Can we Comment on the Weapon and Age of the Stitched Wound? A Case Series - Kavya Sharma; R. Monisha; Sachin Kumar Meena (Indian Journal of Forensic Medicine and Pathology, 2025)
Context: The role of Forensic Expert plays a vital role in the examination and preparing wound certi𿿿cate of every Medico-Legal cases.1 Many times, the victims get the initial treatment in the Private hospital or the casualty, then comes for the medico-legal examination after 3 to 5 days.2 In such cases the problem arises as how to comment upon the contact surface/ weapon when the healing has already started, and margins have become regular. In stitched wounds, many a times the surgeon wound have cleaned the margins, and this further adds the complication to comment upon the weapon. The approximation of the margins depends upon the surgeon’s skills, area of injury, the size of needle used.3 The edges or tailing cannot be made out from the stitched wound most of the times. Many times, the police also seek help from the Medico-legal expert to decide on which IPC section is involved. It relies on the report of Medico-legal expert whether the wound is simple/Grievous caused by non-Dangerous weapon or Dangerous weapon.4 Aims: Through this case series we tried to study the stitched wound of different duration about their margins and edges, and how reliable it is to comment upon the contact surface/ weapon in the stitched wound. Material & Method: Descriptive Observational type of study done at Department of Forensic Medicine, MBS Hospital associated with Governmental Medical College, Kota (Rajasthan), on 10 cases of Stitched wound. Results & Conclusion: we have observed that it is dif𿿿cult to comment upontheweapon from the Stitched wound and the solution is CFMU.5